FORMULATION AND EVALUATION OF BODY SCRUB CREAM FROM CARROT DREGS (Daucus carota L.): FORMULASI DAN EVALUASI KRIM BODY SCRUB DARI AMPAS WORTEL (Daucus carota L.) - Risa Putroe Dalilah; Rina Kurniaty (ROCE : Jurnal Pertanian Terapan, 2025)
Carrot (Daucus carota L.) is one of the natural ingredients that is efficacious to remove dead skin cells and contains many skin nutrients, including β carotene contained in carrots has a brightening effect on the skin which has an important role as a precursor to vitamin A and antioxidants. Carrot pulp is a natural ingredient that can be used as a body scrub cream preparation. This study aims to determine the carrot pulp can be formulated in the preparation of body scrub cream. In this study, 4 formulas were made with variations in concentration F1 (2.5%), F2 (5%) and F3 (7.5%). The preparation tests included organoleptic, homogeneity, pH, spreadability, emulsion type, irritation, and liking tests. The results showed that the preparation made met the physical evaluation of the preparation, namely semi-solid texture, distinctive odor from carrot pulp. Homogeneous preparations, pH ranges from 6.0-6.2 body scrub cream preparations have a spreadability of 5.1-5.5 cm with an oil-in-water. emulsion type, all preparations do not irritate the skin and the irritation index value is equal to 0. The results of the liking test obtained the formula most often preferred by respondents was F3 based on 3 parameters, namely texture, color and aroma of the preparation. The results of the study can be concluded that the formulation and evaluation of body scrub cream preparations from carrot pulp can be combined in body scrub cream preparations